Crosstalk Between microRNAs and the Pathological Features of Secondary Lymphedema - Yusof, Khairunnisa’ Md; Groen, Kira; Rosli, Rozita; Avery-Kiejda, Kelly A. (Frontiers in Cell and Developmental Biology, 2021)
Secondary lymphedema is characterized by lymphatic fluid retention and subsequent tissue swelling in one or both limbs that can lead to decreased quality of life. It often arises after loss, obstruction, or blockage of lymphatic vessels due to multifactorial modalities, such as lymphatic insults after surgery, immune system dysfunction, deposition of fat that compresses the lymphatic capillaries, fibrosis, and inflammation. Although secondary lymphedema is often associated with breast cancer, the condition can occur in patients with any type of cancer that requires lymphadenectomy such as gynecological, genitourinary, or head and neck cancers. MicroRNAs demonstrate pivotal roles in regulating gene expression in biological processes such as lymphangiogenesis, angiogenesis, modulation of the immune system, and oxidative stress. MicroRNA profiling has led to the discovery of the molecular mechanisms involved in the pathophysiology of auto-immune, inflammation-related, and metabolic diseases. Although the role of microRNAs in regulating secondary lymphedema is yet to be elucidated, the crosstalk between microRNAs and molecular factors involved in the pathological features of lymphedema, such as skin fibrosis, inflammation, immune dysregulation, and aberrant lipid metabolism have been demonstrated in several studies. MicroRNAs have the potential to serve as biomarkers for diseases and elucidation of their roles in lymphedema can provide a better understanding or new insights of the mechanisms underlying this debilitating condition.